2013
DOI: 10.1093/aje/kwt292
|View full text |Cite
|
Sign up to set email alerts
|

Reallocating Time to Sleep, Sedentary Behaviors, or Active Behaviors: Associations With Cardiovascular Disease Risk Biomarkers, NHANES 2005–2006

Abstract: Sleep and sedentary and active behaviors are linked to cardiovascular disease risk biomarkers, and across a 24-hour day, increasing time in 1 behavior requires decreasing time in another. We explored associations of reallocating time to sleep, sedentary behavior, or active behaviors with biomarkers. Data (n = 2,185 full sample; n = 923 fasting subanalyses) from the cross-sectional 2005-2006 US National Health and Nutrition Examination Survey were analyzed. The amounts of time spent in sedentary behavior, light… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

25
327
8
7

Year Published

2015
2015
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 348 publications
(367 citation statements)
references
References 26 publications
25
327
8
7
Order By: Relevance
“…Indeed, our substitution analyses indicate that reallocation of sedentary time with LPA could have a favorable effect on reaching glycemic, HDL‐c, and triglyceride control goals. Consistently, the beneficial effects of substituting sedentary time with LPA on cardiometabolic biomarkers were also reported in 2 recent studies 43, 44. In addition, our data also suggest that reallocation of sedentary time with MVPA may help in reaching blood pressure control goals.…”
Section: Discussionsupporting
confidence: 91%
“…Indeed, our substitution analyses indicate that reallocation of sedentary time with LPA could have a favorable effect on reaching glycemic, HDL‐c, and triglyceride control goals. Consistently, the beneficial effects of substituting sedentary time with LPA on cardiometabolic biomarkers were also reported in 2 recent studies 43, 44. In addition, our data also suggest that reallocation of sedentary time with MVPA may help in reaching blood pressure control goals.…”
Section: Discussionsupporting
confidence: 91%
“…Running isotemporal substitution analyses, rather than regression modeling, has been put forward as a suitable analysis method to examine the theoretical effect of substituting one activity, for example, SED with another, for example LIPA, while keeping total time and time in other activities fixed 13 . Previous isotemporal substitution studies, including measurements of glucose regulation and/or insulin sensitivity, have found beneficial associations with SED substitution with standing 14 , LIPA [14][15][16][17] and MVPA 16,17 , respectively, in healthy individuals 14,16 and those at-risk of or with type 2 diabetes.…”
Section: 12mentioning
confidence: 92%
“…The major change is the integration of all movement behaviours across the 24-h period, with the most notable additions being specific recommendations regarding lightintensity physical activity and sleep duration. There is growing evidence that while not as efficacious as MVPA, light-intensity physical activity is associated with some health benefits, especially when it replaces sedentary behaviours (Buman et al 2014;Carson et al 2013bCarson et al , 2016bPoitras et al 2016;Stone and Faulkner 2014), although this area remains relatively understudied. There is also evidence of a "play movement" (Tremblay et al 2015), where activities of all intensities, especially in nature and the outdoors, have been clearly associated with improved health.…”
Section: Research Needsmentioning
confidence: 99%